Digital Health Coaching Programs Among Older Employees in Transition to Retirement: Systematic Literature Review - Stara, Vera; Santini, Sara; Kropf, Johannes; D'Amen, Barbara (JMIR Publications, 2020)
BackgroundThe rapid increase of the aging population is pushing many national governments to reshape retirement legislation in order to extend older adults' working life. Once retired, older adults can be invaluable resources for the community as family carers, as volunteers, or by returning to work. Healthy aging is one of the main conditions for being able to work longer and being active after retirement. The latter, indeed, represents a very sensitive life transition, which can entail psychological and social difficulties. Interventions for promoting older workers' health and well-being and supporting the transition to retirement are on the top of the policy agenda of most European countries. Recently, computer-based and digital health interventions have been seen as promising means to reach this purpose. ObjectiveThis systematic literature review aimed to explore studies on digital health coaching programs for older workers that followed a user-centered design approach and evaluated their effectiveness in providing older adults with guidance for adopting a healthy lifestyle and being active in the community. MethodsThe search identified 1931 papers, and 2 relevant articles were selected by applying specific eligibility criteria. ResultsTo our knowledge, only few digital health coaching programs have targeted the population of older workers to date; there is an insufficient number of studies on the efficacy of such programs. The results show the difficulties of assessing the efficacy of digital coaching itself and with respect to older employees. The 2 studies suggest that digital health programs for workplaces can improve various aspects of older employees' well-being; however, they considered health mainly from a physical perspective and neglected contextual, social, psychological, and cultural factors that can influence older workers' health and general well-being. Future digital health coaching programs should adopt the healthy aging paradigm as a multidimensional lens for interpreting the impact of eHealth technology on aging and retirement. The literature around this issue remains at an embryonic state, and this gap needs to be filled by further investigations that apply a user-centered approach for designing the technology, test innovative research methodologies, and adopt new technical solutions for high-quality interaction design. ConclusionsFurther digital health coaching programs aimed at supporting healthy and active living for older workers and retirees are necessary. The user-centered design approach is recommended in order to fully address the users' health needs and the technological requirements throughout development. Moreover, the healthy aging perspective allows inclusion of physical, social, and psychological factors influencing the transition from work to retirement, as well as the experiences and interactions of individuals with the technology.